Lateral segmental mandibulectomy reconstruction with bridging reconstruction plate and anterolateral thigh free flap: a case series of 30 consecutive patients. Issue 1 (January 2021) - Bowe, C.; Butler, D.; Dhanda, J.; Gulati, A.; Norris, P.; Bisase, B.
Abstract: Lateral posterior segmental mandibular defects present a reconstructive challenge and an osseous flap would be the gold standard to reconstruct such a defect. However, combining a mandibular reconstruction plate (MRP) with a soft-tissue free flap (to restore mucosal integrity and provide durable coverage of the plate itself) offers an alternative option for posterior segmental mandibular defects in patients who are not suitable for osseous reconstruction, or do not choose it. We retrospectively reviewed 30 consecutive patients (19 male and 11 female) who underwent reconstruction of a segmental mandibulectomy defect using a bridging MRP and anterolateral thigh (ALT) free flap. The mean (range) age was 67 (31-87) years. The American Society of Anesthesiologists' (ASA) status of the study population comprised Grade 1 (n = 10), Grade 2 (n = 18), and Grade 3 (n = 2). The majority of patients had oral cavity squamous cell carcinoma (n = 26) involving the mandible, two had osteoradionecrosis, and two mucoepidermoid carcinoma. Four patients had complications specific to the reconstruction, and flap loss occurred in one (96.7% success rate). Metalwork infection occurred in three, including one plate extrusion and one plate fracture. The median length of stay was 10 days, and mean (range) duration of follow up 23.3 (1-96) months. This technique is an alternative reconstructive option for the non-tooth-bearing mandible. Reconstructing a posterolateral segmental mandibulectomy defect with a bridging MRP and ALT free flap offers a robust reconstructive alternative with a favourable complication profile.